2005 ALICE'S ADVENTURES IN WONDERLAND - Sofokleous, Konstantina (My University, 2026)
Animation. An adaptation of Lewis Carroll's original text with symbols and dialogues - Cyprus official representation at the 51st Venice Biennial International Art Exhibition, Biennale Arte 2005, La Biennale di Venezia. Curated by Chus Martinez. Organized by Cyprus Ministry of Education and Culture